Novel and dynamic evolution of equine infectious anemia virus genomic quasispecies associated with sequential disease cycles in an experimentally infected pony. - Leroux, C (1997)
We have investigated the genetic evolution of three functionally distinct regions of the equine infectious anemia virus (EIAV) genome (env, rev, and long terminal repeat) during recurring febrile episodes in a pony experimentally infected with a well-characterized reference biological clone designated EIAV(PV). Viral populations present in the plasma of an EIAV(PV)-infected pony during sequential febrile episodes (18, 34, 80, 106, and 337 days postinfection) were amplified from viral RNA, analyzed, and compared to the inoculated strain. The comparison of the viral quasispecies showed that the inoculated EIAV(PV) quasispecies were all represented during the first febrile episode, but entirely replaced at the time of the second febrile episode, and that new predominant quasispecies were associated with each subsequent cycle of disease. One of the more surprising results was the in vivo generation of large deletion (up to 15 amino acids) in the principal neutralizing domain (PND) of gp90 during the third febrile episode. This deletion did not alter the competence for in vitro replication as shown by the analysis of a env chimeric clone with a partially deleted PND and did not altered the fitness of the virus in vivo, since this partially deleted envelope became the major population during the fourth febrile episode. Finally, we showed that the amino acid mutations were not randomly distributed but delineated eight variables regions, V1 to V8, with V3 containing the PND region. These studies provide the first detailed description of the evolution of EIAV genomic quasispecies during persistent infection and reveal new insights into the genetics and potential mechanisms of lentivirus genomic variation.